Impacto de los créditos otorgados al segmento pymes y su incidencia en la tasa de morosidad de la agencia del Banco Pacifico, Cantón Quevedo, año 2019 – 2020. - Guerrero Ruiz , Joselyne Nathaly (2023)
The right to access a Credit, arises from the need of the human being to seek a future for his family, in our country it is a need that has been perceived as a result of a deep economic crisis that submerged the country, which is why many of the loans have fallen into arrears. Being the main causes of delinquency the misuse of credits since many of them are used for other purposes, they mainly affect the agency's delinquency rate (both due to delinquent balances and the number of operations). research where an interview with the manager and surveys with a questionnaire of questions applied to clients in the SME sector were used. Through the results obtained, the Banco Pacifico Agency of the Quevedo canton has a delinquency of 4.80% for 2019 and in 2020 of 7.23 %, this increase is considered due to the COVID health emergency. In addition, 45% consider that at the moment of making a loan the procedures and delivery times are GOOD and 28% of the clients surveyed stated that the policies and procedures that the institution carries out at the moment that it is in arrears with the credit are few. acceptable.